2017
DOI: 10.1515/biolog-2017-0171
|View full text |Cite
|
Sign up to set email alerts
|

Acid rain-induced oxidative stress regulated metabolic interventions and their amelioration mechanisms in plants

Abstract: Increased anthropogenic environmental pollution, one of the serious threats associated with rapid industrial/ economic development leads to enhanced release of SO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The application of glutathione markedly improves different growth parameters such as plant height and fresh and dry biomass of root and shoot under AR stress through minimizing ROS accumulation and improving the activities of antioxidant enzymes that eventually reduce oxidative stress [ 17 ]. It has been reported that most of the plants could activate their antioxidant system up to a certain level against abiotic stress conditions [ 106 , 107 ]. However, the supplementation of glutathione in AR-stressed plants causes further intensification in the antioxidant activities, possibly owing to the signaling role of applied molecules, and this was confirmed through the transcript profiling of CAT, Mn-SOD , Fe-SOD and Cu/Zn-SOD genes [ 17 ].…”
Section: Effect Of Glutathione In Plants Under Acid Rain Stressmentioning
confidence: 99%
“…The application of glutathione markedly improves different growth parameters such as plant height and fresh and dry biomass of root and shoot under AR stress through minimizing ROS accumulation and improving the activities of antioxidant enzymes that eventually reduce oxidative stress [ 17 ]. It has been reported that most of the plants could activate their antioxidant system up to a certain level against abiotic stress conditions [ 106 , 107 ]. However, the supplementation of glutathione in AR-stressed plants causes further intensification in the antioxidant activities, possibly owing to the signaling role of applied molecules, and this was confirmed through the transcript profiling of CAT, Mn-SOD , Fe-SOD and Cu/Zn-SOD genes [ 17 ].…”
Section: Effect Of Glutathione In Plants Under Acid Rain Stressmentioning
confidence: 99%
“…The emission of the gases has been directly and indirectly correlated with skin, cardiovascular, brain, blood and lung diseases and different types of cancers (Munawer, 2018). Furthermore, acid rains negatively affect soil fertility and the normal functioning of plants at all stages of growth and development by acidifying the soil and surface water, depositing on leaves and changing the symbiotic microbial community (Xalxo and Sahu, 2017). Marine life is also affected by harming the food chain and interferential acid and oxygen circulation, damaging the gills and causing heart problems in fish (Shammas et al, 2020).…”
Section: Acid Rainsmentioning
confidence: 99%
“…Nitrogen oxides (NO x ), as one of the main atmospheric pollutants, are associated with a range of significant environmental concerns. , Carbon monoxide (CO) is another atmospheric pollutant that can bind with hemoglobin in the human body and decreases the oxygen supply.…”
Section: Introductionmentioning
confidence: 99%